THE IMPLEMENTATION OF BBC SIX MINUTES ENGLISH BY EFL TEACHERS’ AS THE TEACHING MEDIA TO TEACH STUDENTS’ LISTENING COMPREHENSION - Novianti, Trisna (NextGen Education Review Journal, 2024)
The purpose of this study is to investigate the implementation of BBC Six Minute English by EFL teachers to teach students' listening comprehension. The study also aims to identify the benefits and challenges encountered by EFL teachers when using BBC Six Minute English in SMA Negeri 9 Cirebon. The research methodology used in this study is descriptive qualitative research. The participants in this study are two EFL teachers. Data collection techniques are carried out through observation and interviews. The results of the study based on observations in the classroom show that there are three stages in teaching listening comprehension using BBC Six Minutes English, namely pre-teaching, during teaching and after teaching. In addition, the results of interviews with two EFL teachers showed that there were four benefits and four challenges felt by EFL teachers when teaching listening comprehension using BBC Six minutes English.